Penerapan Lesson Study Menggunakan Pendekatan Kontekstual dan Kontruktivisme Dipadukan Dengan Model Kooperatif Pada Mata Kuliah Perkembangan Peserta Didik - Herniwati Wahid (Universitas Mathla'ul Anwar Banten, 2015)
The need for a new orientation in education is so strong and evident invarious aspects and fields of study. Educators and educational practitioners already should have toand are able to respond to changes that occur with the changing paradigm of education. Implementation of lesson study learning taught by lecturers of PPKN study program of Cokroaminoto Palopo unversity at student development course. Involving semester 1 students amounted to 42, Male is 18 persons, female is 24 persons. Learning process is scheduled by lecturer team of PPKN study program in November for four meetings. The first and second meetings using contextual approach combined cooperative model, meeting/cycle 3-4 using constructivism approach combined cooperative model. The result of model presenting lecturer activity shows the increasing student activity both in team-work and critically thinking way. Besides improving the quality of learning, attracting and retaining the creativity of the student, paying attention and preparing presentation of teaching aids or other supporting media.